2015
DOI: 10.1111/jvp.12214
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic relationship of marbofloxacin against Aeromonas hydrophila in Chinese soft‐shelled turtles (Trionyx sinensis)

Abstract: The single-dose disposition kinetics of the antibiotic marbofloxacin were determined in Chinese soft-shelled turtles (n = 10) after oral and intramuscular (i.m.) dose of 10 mg/kg bodyweight. The in vitro and ex vivo activities of marbofloxacin in serum against a pathogenic strain of Aeromonas hydrophila were determined. A concentration-dependent antimicrobial activity of marbofloxacin was confirmed for levels lower than 4 × MIC. For in vivo PK data, values of AUC: minimum inhibitory concentration (MIC) ratio f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…A. hydrophila is common to infect turtles, fish and other amphibians as well as humans, as it is widely distributed in fresh water, estuarine and marine environments [138,139]. Among turtles, A. hydrophila infections were reported in Pseudemis scripta [140] and soft-shelled turtles (Trionyx sinensis) [141][142][143]. In the 1994 outbreak of A. hydrophila in Italy, there was a 95% mortality rate and the autopsies revealed infection in visceral organs [140].…”
Section: Discussionmentioning
confidence: 99%
“…A. hydrophila is common to infect turtles, fish and other amphibians as well as humans, as it is widely distributed in fresh water, estuarine and marine environments [138,139]. Among turtles, A. hydrophila infections were reported in Pseudemis scripta [140] and soft-shelled turtles (Trionyx sinensis) [141][142][143]. In the 1994 outbreak of A. hydrophila in Italy, there was a 95% mortality rate and the autopsies revealed infection in visceral organs [140].…”
Section: Discussionmentioning
confidence: 99%
“…() and Shan et al. (). In brief, ENR solution(2 ml; in MHB or serum)at twice the required final maximum concentration was added to 1 ml of MHB or serum.…”
Section: Methodsmentioning
confidence: 99%
“…In pharmacokinetic studies involving other reptile species, and similarly to other quinolones, MBX has demonstrated to be a lipid‐soluble organic acid with good tissue penetration (concentrations normally exceeding those in plasma) and volumes of distribution in excess of body water volume (>1 L/kg): in Trachemys scripta scripta 1.59 ± 1.47, 1.52 ± 1.17, and 0.47 ± 0,46 L/kg after intracoelomic dose of 0.4, 2, and 10 mg/kg, respectively (Vercelli et al, ); in Tryonix sinensis 2.43 and 4.66 L/kg after IM and PO dose of 10 mg/kg (Shan et al, ); 1.45 ± 0.24 L/kg after IM dose of 2 mg/kg in Crocodylus siamensis (Poapolathep et al, ). In the present study, the apparent volume of distribution resulted particularly low (100.90 ± 27.83, 372.42 ± 100.17 and 660.64 ± 83.12 ml/kg after IV, IM in forelimb and in IM in hindlimb, respectively), suggesting a scarce tissue distribution or a low accumulation of the drug in specific organs.…”
Section: Discussionmentioning
confidence: 99%